2003
DOI: 10.4269/ajtmh.2003.69.87
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Basophilia in Human Parasitic Infections

Abstract: While basophilia is often found in animal models of parasitic infection, it has not yet been established whether it occurs in parasite-infected humans. We investigated the relationship between basophilia and parasitic infections in humans by reviewing charts from 668 patients with confirmed parasitic infection (472 with only helminths, 146 with only protozoa, and 50 with both helminth and protozoan infections) and from 50 patients without parasitic infections. Basophilia (> 290 cells/mm3) occurred in only four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…In mice infected with N. brasiliensis basophils have been identified as the main IL-4-producing cell type [61] and similar findings were found in humans during filarial infections [62]. While systemic basophilia appears to be less prominent in humans (though it has been observed in N. americanus infections), basophils react to a wide variety of antigens in Schistosoma-, Toxocaria-, Wuchereria-, Strongyloides-, Onchocerca-and Ascaris-infected patients [63]. Of interest concerning a possible innate role for basophils here is that basophils from non-immune donors release substantial amounts of IL-4 (and other mediators) to certain parasitic products, as has been shown using Schistosoma mansoni egg antigen as well as Echinococcus multicularis metacestode extract [64][65][66].…”
Section: Do Basophils Also Participate In Innate Immunity?supporting
confidence: 52%
“…In mice infected with N. brasiliensis basophils have been identified as the main IL-4-producing cell type [61] and similar findings were found in humans during filarial infections [62]. While systemic basophilia appears to be less prominent in humans (though it has been observed in N. americanus infections), basophils react to a wide variety of antigens in Schistosoma-, Toxocaria-, Wuchereria-, Strongyloides-, Onchocerca-and Ascaris-infected patients [63]. Of interest concerning a possible innate role for basophils here is that basophils from non-immune donors release substantial amounts of IL-4 (and other mediators) to certain parasitic products, as has been shown using Schistosoma mansoni egg antigen as well as Echinococcus multicularis metacestode extract [64][65][66].…”
Section: Do Basophils Also Participate In Innate Immunity?supporting
confidence: 52%
“…This correlation exists in various diseases, including in helminth-infected individuals [73]. Although there appears to be no correlation between blood basophilia and helminth infection, basophils are involved in the initiation and execution of an effective immune response against helminths [74]. Moreover, basophils have been observed to peak during the period of N. brasiliensis expulsion, during N. americanus infection in humans and after effective chemotherapy [75].…”
Section: Role Of Basophils During Helminth Infectionmentioning
confidence: 97%
“…Indeed a worldwide study of basophilia in different helminth infections showed that IgE and eosinophils were raised in all 668 confirmed helminth‐infected patients even if they had concurrent protozoal infections, while people infected with protozoal infections alone or uninfected people did not have raised eosinophils or IgE. In contrast, basophils were raised in only four helminth‐infected patients (172).…”
Section: Basophilia During Infection With Helminthsmentioning
confidence: 99%